2018
DOI: 10.5534/wjmh.17028
|View full text |Cite
|
Sign up to set email alerts
|

Udenafil, a Phosphodiesterase 5 Inhibitor, Reduces Body Weight in High-Fat-Fed Mice

Abstract: PurposeHigh-fat (HF) feeding induces hypothalamic leptin resistance via the activation of toll-like receptor 4 (TLR4). TLR4 deficiency confers resistance to diet-induced obesity. Udenafil, an anti-impotence drug, inhibits TLR4 in airway epithelial cells in vitro. In this study, we evaluated whether udenafil suppressed the hypothalamic expression of TLR4 and reduced body weight.Materials and MethodsThe hypothalamic expression of TLR4, phosphodiesterase 5 (PDE5), nuclear factor-κB (NF-κB), and myeloid differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 30 publications
0
9
0
2
Order By: Relevance
“…It is characterized by high blood sugar and insulin resistance [64]. In this population, PDE5i (particularly tadalafil and sildenafil) have been proven not only to be safe in diabetic men experiencing ED [59,65,66] but also to directly control metabolism regulation as T2DM tends to ameliorate after specific PDE5 inhibition (Figure 2) [20,22]. Several studies have focused on the use of the PDE5i to treat inflammation, vascular injury, and hepatic diseases often associated with diabetes in both animal models and humans [67][68][69].…”
Section: Pde5 Inhibitors and Diabetesmentioning
confidence: 99%
See 2 more Smart Citations
“…It is characterized by high blood sugar and insulin resistance [64]. In this population, PDE5i (particularly tadalafil and sildenafil) have been proven not only to be safe in diabetic men experiencing ED [59,65,66] but also to directly control metabolism regulation as T2DM tends to ameliorate after specific PDE5 inhibition (Figure 2) [20,22]. Several studies have focused on the use of the PDE5i to treat inflammation, vascular injury, and hepatic diseases often associated with diabetes in both animal models and humans [67][68][69].…”
Section: Pde5 Inhibitors and Diabetesmentioning
confidence: 99%
“…Different studies performed in diet-induced obese animal models have investigated the effects of a new PDE5i, DA-8159, as well as the PDE5i udenafil. In these studies, the authors demonstrated that the oral administration of PDE5i ameliorated body weight, plasma cholesterol and triglyceride levels, visceral fat mass, cumulative caloric intake, and plasma leptin concentration in comparison with vehicle-treated mice [ 58 , 59 ].…”
Section: Pde5 Inhibitors and Insulin Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…Активно обсуждается роль системного воспаления в патогенезе ЭД, ассоциированной с ожирением. Свободные жирные кислоты активируют Toll-подобные рецепторы, запуская внутриклеточный сигнальный каскад с участием большого количества разнообразных провоспалительных цитокинов [5]. Провоспалительные цитокины, в свою очередь, подавляют каскад эндотелиальной NO-синтазы и провоцируют тем самым эндотелиальную дисфункцию [6].…”
Section: научный обзорunclassified
“…GCTTGGTCTTGAATGAAGTCA, successfully demonstrated that udenafil suppresses TLR4 mRNA expression in the hypothalamus [9]. Another study conducted by Fiore et al (2018) with sequence forward: GGAGGAGAATACTGGCAAGA, reverse: GATGCATGGTAAGACAGGAC; in type 2 diabetic mice administrated sildenafil for 12 weeks could increase adipogenesis and improve adipose tissue [10].…”
Section: Introductionmentioning
confidence: 96%